2006
DOI: 10.1007/s10681-005-9063-6
|View full text |Cite
|
Sign up to set email alerts
|

Introgression of Cajanus platycarpus genome into cultivated pigeonpea, C. cajan

Abstract: SummaryCajanus platycarpus, an incompatible wild species from the tertiary gene pool of pigeonpea (C. cajan (L.) Millspaugh), has many desirable characteristics for the improvement of cultivated varieties. To necessitate such transfers, embryo rescue techniques were used to obtain F 1 hybrids. The F 1 hybrids were treated with colchicine to obtain tetraploid hybrids, that were selfed to obtain F 2 , F 3 and F 4 progenies. All of the hybrids and subsequent progenies had an intermediate morphology between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 7 publications
0
43
0
Order By: Relevance
“…These studies also revealed that two of the wild relatives, C. cajanifolius and C. scarabaeoides, are closely related to pigeonpea. Cytological studies have also proved that C. cajanifolius is the progenitor species of C. cajan, as both species have similar karyotypes, and the hybrids produced from crossing the two species have normal meiosis with high pollen fertility (Pundir and Singh, 1985;Mallikarjuna et al, 2006). Pigeonpea (Cajanus cajan) is a short-lived perennial shrub that is cultivated as an annual grain legume crop in tropical and subtropical regions.…”
Section: Crop Pigeonpea (Cajanus Cajan L)mentioning
confidence: 99%
“…These studies also revealed that two of the wild relatives, C. cajanifolius and C. scarabaeoides, are closely related to pigeonpea. Cytological studies have also proved that C. cajanifolius is the progenitor species of C. cajan, as both species have similar karyotypes, and the hybrids produced from crossing the two species have normal meiosis with high pollen fertility (Pundir and Singh, 1985;Mallikarjuna et al, 2006). Pigeonpea (Cajanus cajan) is a short-lived perennial shrub that is cultivated as an annual grain legume crop in tropical and subtropical regions.…”
Section: Crop Pigeonpea (Cajanus Cajan L)mentioning
confidence: 99%
“…van der Maesen (Saxena et al 2010a, b), A 7 CMS system from C. platycarpus (Benth.) van der Maesen (Mallikarjuna et al 2006) and most recently A 8 CMS system from C. reticulatus (Dryander) F. V. Muell. (Saxena 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some lines have shown a high level of resistance to pod borers, pod fly and bruchids under unprotected field conditions. Out of the 21 wild species in the tertiary gene pool of pigeonpea, only C. platycarpus has been utilized for improving insect resistance through inter-specific hybridization [66,67]. It (C. platycarpus) is a species of interest to pigeonpea breeders because it has various traits of interest [31].…”
Section: Utilization Of Wild Resources For Introgression Of Resistancementioning
confidence: 99%